Solid electrolyte membrane, preparation method thereof and lithium ion battery
A composite solid electrolyte membrane with a polymer and ceramic-filled layer, prepared via a wet process, addresses the limitations of ceramic sintering by enhancing ionic conductivity and flexibility, improving battery cycle performance and reducing energy consumption.
Patent Information
- Application Number
- CN202411364463.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-05
- Publication Date
- 2025-01-03
AI Technical Summary
Existing solid-state lithium-ion batteries face challenges with high energy consumption, poor interface contact, and limited cycle performance due to the use of ceramic sintering methods for solid electrolyte membranes, which are costly and time-consuming, and lack sufficient ionic conductivity and flexibility.
A composite solid electrolyte membrane comprising a first polymer layer with lithium salt and a second ceramic-filled polymer layer, utilizing ethyl or propyl cellulose, is prepared via a wet process, allowing for better ionic conductivity and flexibility, and can be formed at room temperature, enhancing battery cycle performance.
The composite membrane improves battery cycle performance by efficiently conducting lithium ions, reducing the risk of short circuits, and lowering energy consumption and production costs, with stable operation at 0.33C and over 100 cycles for Li\NMC811 batteries.
Smart Images

Figure BDA0005066458010000171 
Figure BDA0005066458010000181 
Figure BDA0005066458010000191
Abstract
Description
[0001] This application is a divisional application. The application number of the original application is: 202410724192.4, the application date is June 5, 2024, and the name of the invention is: Solid electrolyte membrane, preparation method thereof and lithium-ion battery. Technical Field
[0002] The present application relates to the field of battery technology, and in particular to a solid electrolyte membrane and a preparation method thereof, and a lithium-ion battery. Background Art
[0003] In recent years, solid-state lithium-ion batteries have gradually attracted attention due to the use of solid electrolytes to replace electrolytes and separators, making the batteries thinner, smaller in size, and safer. As an important component of the battery, the solid electrolyte membrane affects the battery's cycle performance. Therefore, it is necessary to develop a higher-performance solid electrolyte membrane. Summary of the invention
[0004] The embodiments of the present application provide a solid electrolyte membrane and a preparation method thereof and a lithium-ion battery, aiming to provide a solid electrolyte membrane with high ionic conductivity.
[0005] In a first aspect, an embodiment of the present application provides a solid electrolyte membrane, comprising a first membrane layer and a second membrane layer stacked together, wherein:
[0006] The material of the first film layer includes a first polymer and a lithium salt;
[0007] The material of the second film layer includes an inorganic ceramic filler, a second polymer and cellulose;
[0008] Wherein, the cellulose includes one or more of ethyl cellulose and propyl cellulose;
[0009] The first polymer and the second polymer are independently selected from one or more of PVDF and PVDF-HFP.
[0010] Optionally, in some embodiments of the present application, the first polymer is selected from PVDF; and / or, the second polymer is selected from PVDF-HFP; and / or,
[0011] The lithium salt includes one or more of LiTFSI, LiFSI, and LiC 1O 4 ; and / or, the inorganic ceramic filler includes one or more of LLZTO and LLZGO.
[0012] Optionally, in some embodiments of the present application, in the material of the first film layer, the mass ratio of the first polymer to the lithium salt is (6-8):(2-3); and / or,
[0013] In the material of the second film layer, the mass ratio of the inorganic ceramic filler to the second polymer is (30-31):(0.62-2); and / or,
[0014] In the material of the second film layer, the mass ratio of the inorganic ceramic filler to the cellulose is (30-31):(6-7).
[0015] Optionally, in some embodiments of the present application, the thickness of the first film layer is 10 to 20 μm; and / or the thickness of the second film layer is 30 to 45 μm.
[0016] In a second aspect, an embodiment of the present application provides a method for preparing a solid electrolyte membrane, comprising the following steps:
[0017] Providing a first substrate, a second substrate, a first slurry and a second slurry;
[0018] coating the first slurry on the first substrate to form a first film layer;
[0019] coating the second slurry on the second substrate to form a second film layer; and,
[0020] The first film layer and the second film layer are stacked to form a solid electrolyte membrane;
[0021] The first slurry includes a first polymer, a lithium salt and a first solvent, the second slurry includes an inorganic ceramic filler, a second polymer, cellulose and a second solvent, the cellulose includes one or more of ethyl cellulose and propyl cellulose, and the first polymer and the second polymer are independently selected from one or more of PVDF and PVDF-HFP.
[0022] Optionally, in some embodiments of the present application, the first solvent includes one or more of DMF and tetrahydrofuran; and / or,
[0023] The second solvent comprises ethanol; and / or,
[0024] The first polymer is selected from PVDF; and / or,
[0025] The second polymer is selected from PVDF-HFP; and / or,
[0026] The lithium salt includes one or more of LiTFSI, LiFSI, LiC 1O 4 ; and / or,
[0027] The inorganic ceramic filler includes one or more of LLZTO and LLZGO.
[0028] Optionally, in some embodiments of the present application, the first slurry comprises the following components, measured by mass percentage: 6-8% of a first polymer, 2-3% of a lithium salt, and the remainder being a first solvent; and / or,
[0029] Calculated by mass percentage, the second slurry includes the following components: 30-31% inorganic ceramic filler, 0.62-2% second polymer, 6-7% cellulose, and the balance is a second solvent.
[0030] Optionally, in some embodiments of the present application, the step of coating the second slurry on the second substrate to form a second film layer includes: coating the second slurry on the first film layer, and then standing at 10-40° C. for 30-60 minutes to obtain the second film layer.
[0031] Optionally, in some embodiments of the present application, the step of coating the first slurry on the first substrate to form a first film layer includes: coating the first slurry on the first substrate, and then heating at 60 to 80° C. for 120 to 180 minutes to obtain the first film layer.
[0032] In a third aspect, an embodiment of the present application provides a lithium-ion battery, comprising a positive electrode and a negative electrode arranged opposite to each other, and a solid electrolyte membrane arranged between the positive electrode and the negative electrode, wherein the solid electrolyte membrane comprises the solid electrolyte membrane described above, or is prepared by the preparation method described above, and the first film layer of the solid electrolyte membrane is arranged toward the negative electrode.
[0033] The technical solution provided in the present application provides a solid electrolyte membrane, which has good ionic conductivity, can efficiently conduct lithium ions, and after being assembled into a battery, can greatly improve the battery cycle. In addition, in the solid electrolyte membrane, the material of the second membrane layer can be well dispersed in ethanol, and the prepared slurry not only has good film-forming and film-removable properties, but also can effectively achieve film formation at room temperature, which helps to reduce the energy consumption of film making. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0035] Figure 1 A schematic diagram of the structure of a solid electrolyte membrane provided in an embodiment of the present application;
[0036] Figure 2 A schematic diagram of the structure of a lithium-ion battery provided in an embodiment of the present application;
[0037] Figure 3 A schematic flow chart of a method for preparing a solid electrolyte membrane provided in an embodiment of the present application; Figure numbers: 100 - solid electrolyte membrane; 10 - first membrane layer; 20 - second membrane layer; 200 - lithium-ion battery; 30 - negative electrode; 40 - positive electrode. DETAILED DESCRIPTION
[0038] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.
[0039] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art, and the materials or reagents used in the examples and comparative examples of the present application are commercially available. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present application. The preferred implementation methods and materials described herein are for demonstration purposes only and cannot limit the content of the present application.
[0040] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. The various embodiments of the present application may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any cited numbers (fractions or integers) within the indicated range.
[0041] In the description of the present application, the term “including” means “including but not limited to”.
[0042] The terms "multiple", "multiple times" or similar expressions refer to two (times) or more than two (times), for example, it can be two (times), three (times), four (times), five (times), six (times), etc.
[0043] The selection scope of the term "and / or" includes any one of two or more related listed items, and also includes any and all combinations of the related listed items, and the said any and all combinations include any combination of two related listed items, any more related listed items, or all related listed items. For example, "A and / or B" includes three parallel solutions of A, B and A+B. For another example, the technical solution of "A, and / or, B, and / or, C, and / or, D" includes any one of A, B, C, and D (that is, the technical solution connected by "logical or"), and also includes any and all combinations of A, B, C, and D, that is, the combination of any two or any three of A, B, C, and D, and also includes the combination of four items of A, B, C, and D (that is, the technical solution connected by "logical and").
[0044] The term "solid content" refers to the ratio of the mass of solid matter in the slurry to the total mass of the slurry.
[0045] In a first aspect, the present application embodiment provides a solid electrolyte membrane 100, see Figure 1 , the solid electrolyte membrane 100 includes a first film layer 10 and a second film layer 20 stacked. The material of the first film layer 10 includes a first polymer and a lithium salt; the material of the second film layer 20 includes an inorganic ceramic filler, a second polymer and cellulose; wherein the cellulose includes one or more of ethyl cellulose and propyl cellulose; the first polymer and the second polymer are independently selected from one or more of PVDF (polyvinylidene fluoride) and PVDF-HFP (poly (vinylidene fluoride-co-hexafluoropropylene)). In the related art, the solid electrolyte membrane 100 is often prepared by a ceramic sintering method. However, this method is not only costly, time-consuming and costly, but also has the problems of poor strength and poor contact with the interface performance of the positive electrode 40 in the simple ceramic oxide molding. The solid electrolyte membrane 100 provided in the present application not only has better ionic conductivity, can efficiently conduct lithium ions, and after being assembled into a battery, can greatly improve the cycle of the battery, but also has better flexibility, which can make up for the strength problem of pure ceramic electrolyte. In addition, since the material of the second membrane layer 20 in the solid electrolyte membrane 100 provided in the present application can be well dispersed in ethanol, and the prepared slurry not only has better film-forming and film-removable properties, but also can form a film at room temperature, the solid electrolyte membrane 100 proposed in the present application can be prepared by a wet process at a lower temperature, which helps to reduce the energy consumption and difficulty of membrane making.
[0046] In the solid electrolyte membrane 100 provided in this embodiment, the first membrane layer 10, as a pure polymer membrane, has the characteristics of strong flexibility and high density, can inhibit the further growth of lithium dendrites on the side of the lithium metal negative electrode 30, prevent the electrolyte membrane from piercing and causing a short circuit, and at the same time isolate the byproducts on the lithium metal side from diffusing to the electrolyte membrane. The second membrane layer 20, as a composite ceramic electrolyte membrane, has high ionic conductivity and can effectively conduct lithium ions. The composite membrane formed by the first membrane layer 10 and the second membrane layer 20 not only has high ionic conductivity and better transmission performance, but also can reduce the risk of short circuit caused by lithium dendrites piercing the electrolyte membrane. When used as an electrolyte membrane for a lithium battery, it can greatly improve the cycle of the battery. In some embodiments, the battery made using the solid electrolyte membrane 100 can operate stably at 0.33C, and the assembled Li\NMC811 battery can be stably cycled for more than 100 cycles.
[0047] After the first polymer is formed into a film, it can isolate the lithium metal negative electrode 30 from the electrolyte membrane, and prevent the lithium metal from passing through the electrolyte membrane and causing a short circuit. In some embodiments, the first polymer is selected from PVDF. In comparison, when the first polymer is selected from PVDF, it can form a better film, improve the flexibility and density of the film layer, better isolate the lithium metal negative electrode 30 from the electrolyte membrane, and help improve the cycle performance of the battery.
[0048] The second polymer helps to bond ceramic particles to assist film formation and form an electrolyte membrane with high ionic conductivity. In some embodiments, the second polymer is selected from PVDF-HFP. In comparison, when the second polymer is selected from PVDF-HFP, it has better matching with other materials in the same layer, is more conducive to improving the cycle performance of the battery, and is more suitable for ethanol solvent, which is conducive to film formation of the membrane layer at room temperature.
[0049] In other embodiments, the first polymer is selected from PVDF, and the second polymer is selected from PVDF-HFP. In this way, it is helpful to greatly improve the overall performance of the solid electrolyte membrane 100 and enhance the cycle performance of the battery. Among them, cellulose can play the role of bonding support in the membrane layer, which helps to improve the uniformity and density of the film formation of the membrane layer. In comparison, ethyl cellulose and propyl cellulose have better matching with other materials in the same membrane layer, which is more conducive to the improvement of film forming effect and electrolyte membrane performance. Moreover, these two materials have better solubility in ethanol, which is conducive to the film formation of the membrane layer at room temperature. In addition, in the solid electrolyte membrane 100 of the present application, the setting of the first membrane layer 10 and the second membrane layer 20 is also more conducive to increasing the proportion of cellulose, thereby facilitating the film formation of the electrolyte.
[0050] In some embodiments, the lithium salt includes one or more of Li TFS I (lithium bis(trifluoromethylsulfonyl)imide), Li FS I (lithium bis(fluorosulfonyl)imide), and Li C l O4 (lithium perchlorate), which helps to increase the lithium ion concentration in the film layer, improve the ionic conductivity of the first film layer 10, and help form a stable SE I layer (solid electrolyte interface layer).
[0051] In some embodiments, the inorganic ceramic filler includes one or more of LLZTO (tantalum-doped lithium lanthanum zirconium oxide) and LLZGO (gallium-doped lithium lanthanum zirconium oxide), which is more conducive to improving ionic conductivity.
[0052] In some embodiments, in the material of the first film layer 10, the mass ratio of the first polymer to the lithium salt is (6-8): (2-3); for example, it can be 6:2, 6:2.3, 6:2.5, 6:2.7, 6:3, 7:2, 7:2.1, 7:2.5, 7:2.8, 7:3, 8:2, 8:2.2, 8:2.5, 8:2.9, 8:3, etc. Controlling the mass ratio within this range is helpful to improve the strength of the film layer, enhance the uniformity of film formation and the removability of the film layer, and is more conducive to improving battery performance.
[0053] In some embodiments, in the material of the second film layer 20, the mass ratio of the inorganic ceramic filler to the second polymer is (30-31): (0.62-2); for example, it can be 30:0.62, 30:0.8, 30:1, 30:1.1, 30:1.3, 30:1.5, 30:1.8, 30:1.9, 30:2, 30.5:0.62, 30.5:1, 30.5:1.2, 30.5:1.5, 30.5:2, 30.8:1, 30.9:1.5, 30.3:2, 31:0.62, 31:1, 31:1.5, 31:1.8, 31:2, etc. Controlling the mass ratio within this range helps to improve the uniformity of film formation and the removability of the film layer, and is more conducive to improving battery performance.
[0054] In some embodiments, in the material of the second film layer 20, the mass ratio of the inorganic ceramic filler to the cellulose is (30-31): (6-7); for example, it can be 30:6, 30:6.2, 30:6.4, 30:6.5, 30:6.8, 30:6.9, 30:7, 30.5:6, 30.5:6.5, 30.5:6.7, 30.5:7, 30.4:6, 30.9:6.5, 30.8:7, 31:6, 31:6.5, 31:6.8, 31:7, etc. Controlling the mass ratio within this range helps to improve the uniformity of film formation and the removability of the film layer, and is more conducive to improving battery performance.
[0055] In some embodiments, the thickness of the first film layer 10 is 10-20 μm, for example, 10 μm, 12 μm, 14 μm, 15 μm, 16 μm, 18 μm, 20 μm, and any value between the above two values. In some embodiments, the thickness of the second film layer 20 is 30-45 μm, for example, 30 μm, 32 μm, 34 μm, 35 μm, 36 μm, 37 μm, 40 μm, 42 μm, 45 μm, and any value between the above two values.
[0056] In a second aspect, the present application also provides a method for preparing a solid electrolyte membrane 100, see Figure 3 , the preparation method comprises the following steps:
[0057] S10, providing a first substrate, a second substrate, a first slurry, and a second slurry;
[0058] S20, coating the first slurry on the first substrate to form a first film layer 10;
[0059] S30, coating the second slurry on the second substrate to form a second film layer 20;
[0060] S40, the first membrane layer 10 and the second membrane layer 20 are stacked to form a solid electrolyte membrane 100;
[0061] The first slurry includes a first polymer, a lithium salt and a first solvent, the second slurry includes an inorganic ceramic filler, a second polymer, cellulose and a second solvent, the cellulose includes one or more of ethyl cellulose and propyl cellulose, and the first polymer and the second polymer are independently selected from one or more of PVDF and PVDF-HFP.
[0062] The preparation method proposed in this application adopts a wet process to prepare the solid electrolyte membrane 100, which has simple steps and is easy to implement, and the formation process of the second membrane layer 20 can be carried out at room temperature, which greatly reduces the difficulty and energy consumption of membrane preparation and reduces the cost. In addition, the solid electrolyte membrane 100 prepared by the preparation method of this application has better ionic conductivity and can efficiently conduct lithium ions. After being assembled into a battery, it can greatly improve the cycle of the battery.
[0063] Among them, the first substrate and the second substrate are used to prepare and carry the first film layer 10 and the second film layer 20 respectively, which can specifically be any plate material with a flat surface for film formation, such as a PET substrate, aluminum foil, glass substrate, etc. The first substrate and the second substrate can be the same or different. In some embodiments, the first substrate and the second substrate can also be any prepared film layer, such as the first film layer 10, the second film layer 20, the positive electrode 40, the negative electrode 30, etc. In some embodiments, the first film layer 10 can be prepared first, and then the second film layer 20 can be prepared on the surface of the first film layer 10 to obtain a solid electrolyte membrane 100 with a stacked structure; or the second film layer 20 can be prepared first, and then the first film layer 10 can be prepared on the surface of the second film layer 20 to obtain a solid electrolyte membrane 100 with a stacked structure.
[0064] In the embodiment of the present application, the first film layer 10 and the second film layer 20 may also be prepared on different substrates respectively, and then stacked to form the solid electrolyte membrane 100 after film stripping, which helps to improve the film formation quality of each film layer.
[0065] In some embodiments, the second solvent includes ethanol, which can not only disperse other components of the second slurry well and volatilize at room temperature, but also make the slurry prepared therefrom have suitable film-forming and removable properties, and can prepare a second film layer 20 that is easy to remove and has uniform film formation.
[0066] In some embodiments, the second polymer is selected from PVDF-HFP. PVDF-HFP not only has good compatibility with other materials in the same layer, which is beneficial to improving the cycle performance of the battery, but also can be well dissolved in ethanol, which is conducive to film formation at room temperature and improves the film formation effect.
[0067] In some embodiments, the inorganic ceramic filler includes one or more of LLZTO and LLZGO.
[0068] In some embodiments, the first solvent comprises one or more of DMF and tetrahydrofuran.
[0069] In some embodiments, the first polymer is selected from PVDF.
[0070] In some embodiments, the lithium salt includes one or more of LiTFSI, LiFSI, and LiC 1O 4 .
[0071] In some embodiments, the first slurry includes the following components by mass percentage: 6-8% first polymer, 2-3% lithium salt, and the balance is the first solvent. For example, the first slurry may include 6% first polymer, 2% lithium salt and 92% first solvent, 6.5% first polymer, 3% lithium salt and 90.5% first solvent, 7% first polymer, 2.5% lithium salt and 90.5% first solvent, or 6.2% first polymer, 2.6% lithium salt and 91.2% first solvent, and so on. According to a suitable ratio, the first polymer, lithium salt and first solvent are uniformly mixed to obtain a first slurry, and the first slurry can be applied to form a first film layer 10. In some embodiments, in the first film layer 10, the mass ratio of the first polymer to the lithium salt is (6-8): (2-3).
[0072] In terms of mass percentage, the second slurry includes the following components: 30-31% inorganic ceramic filler, 0.62-2% second polymer, 6-7% cellulose, and the balance is a second solvent. For example, the second slurry may include 30% inorganic ceramic filler, 2% second polymer, 6% cellulose and 62% second solvent, 30.5% inorganic ceramic filler, 1.8% second polymer, 6.5% cellulose and 61.2% second solvent, 31% inorganic ceramic filler, 1.5% second polymer, 6.7% cellulose and 60.8% second solvent, 30.8% inorganic ceramic filler, 1.2% second polymer, 7% cellulose and 61% second solvent, and so on. In an appropriate proportion, the inorganic ceramic filler, the second polymer, the cellulose and the second solvent are uniformly mixed to obtain a second slurry, and the second slurry can form a second film layer 20 after coating. In some embodiments, in the second film layer 20, the mass ratio of the inorganic ceramic filler to the second polymer is (30-31):(0.62-2); the mass ratio of the inorganic ceramic filler to the cellulose is (30-31):(6-7).
[0073] In some embodiments, the step of coating the second slurry on the first film layer 10 to form the second film layer 20 includes: coating the second slurry on the first film layer 10, and then standing at 10-40° C. for 30-60 minutes to obtain the second film layer 20. The second slurry has good film-forming and film-removable properties, can be left to stand at a lower temperature to form a film, and has a good film-forming effect, thereby reducing the energy consumption of film making.
[0074] In some embodiments, the step of coating the first slurry on the first substrate to form the first film layer 10 includes: coating the first slurry on the first substrate, and then heating at 60 to 80° C. for 120 to 180 minutes to obtain the first film layer 10 .
[0075] In step S40, the first film layer 10 and the second film layer 20 are stacked, for example, the first film layer 10 can be stacked on the second film layer 20, or the second film layer 20 can be stacked on the first film layer 10, and the two layers of film are pressed into shape under the action of external force to obtain the solid electrolyte membrane 100. Alternatively, when preparing the lithium-ion battery 200, the two film layers, the positive electrode 40, and the negative electrode 30 can be stacked and assembled in sequence, and then pressed or wound into a battery cell.
[0076] In a third aspect, the present application also provides a lithium-ion battery 200, including but not limited to a button battery, a soft-pack battery, a square lithium-ion battery 200, a cylindrical lithium-ion battery 200, etc. Figure 2 The lithium-ion battery 200 includes a positive electrode 40 and a negative electrode 30 arranged opposite to each other, and a solid electrolyte membrane 100 arranged between the positive electrode 40 and the negative electrode 30, wherein the solid electrolyte membrane 100 includes the solid electrolyte membrane 100 as described in any embodiment of the foregoing text, or the solid electrolyte membrane 100 is prepared by the preparation method as described in any embodiment of the foregoing text, wherein the first film layer 10 of the solid electrolyte membrane 100 is arranged toward the negative electrode 30, and the second film layer 20 is arranged close to the positive electrode 40.
[0077] The technical scheme and technical effects of the present application are described in detail below through specific embodiments. The following embodiments are only some embodiments of the present application and do not specifically limit the present application.
[0078] Example 1
[0079] The structure of the solid electrolyte membrane provided in this embodiment is:
[0080] The materials of the first membrane layer are PVDF and Li TFS I, and the mass ratio of PVDF to Li TFS I is 6.6:2.2. The solvent used in the preparation is DMF, and the proportions of each component in the prepared slurry are: PVDF 7.4wt%, Li TFS I2.48wt%, and DMF 90.09wt%.
[0081] The materials of the second film layer are Ga-LLZO ceramic, PVDF-HFP and ethyl cellulose, and the mass ratio of the three is 5:0.1:1. The solvent used in the preparation is ethanol, and the proportion of each component in the prepared slurry is approximately: Ga-LLZO ceramic 31.06wt%, PVDF-HFP 0.62wt%, ethyl cellulose 6.21wt%, ethanol 62.11wt%.
[0082] (I) The preparation steps of the solid electrolyte membrane are as follows:
[0083] 1. Using a wet molding process, 0.66g PVDF and 0.22g Li TFS I were dissolved in 8g DMF, and stirred at room temperature (about 20°C) for 8h to obtain a uniform solution; the uniform solution was taken and coated on a glass plate by a solution casting-drying method using a 150μm scraper, and then dried at 80°C for 180min to obtain a first film layer with a thickness of about 15μm;
[0084] 2. Stir and dissolve 0.5g ethyl cellulose and 5g ethanol in a homogenizer, then add 2.5g Ga-LLZO ceramics and 0.05g PVDF-HFP polymer, and continue to mix them evenly using a homogenizer to form a uniform slurry. Use a 150μm scraper to scrape the slurry onto the PET film, wait for it to dry and demold at room temperature (about 20°C) to obtain a second film layer. The thickness of the second film layer after demolding is about 35μm.
[0085] 3. Directly overlap and stack the above two layers of film, and when assembling the battery, make the first film layer contact with the lithium metal negative electrode, and make the second film layer contact with the positive electrode.
[0086] Example 2
[0087] This embodiment is substantially the same as Embodiment 1, with the only difference being that in this embodiment: the thickness of the second film layer is approximately 45 μm.
[0088] Example 3
[0089] This embodiment is basically the same as Embodiment 1, except that, in this embodiment: the components in the slurry of the second membrane layer account for approximately 30wt% Ga-LLZO ceramic, 2wt% PVDF-HFP, 6wt% ethyl cellulose and 62wt% ethanol.
[0090] Example 4
[0091] This embodiment is basically the same as embodiment 1, the only difference being that in the second film layer of this embodiment, cellulose is replaced by propyl cellulose, and corresponding adjustments are made in preparation step 2.
[0092] Apart from this, all other parameters and steps remain unchanged.
[0093] Example 5
[0094] This embodiment is basically the same as Embodiment 1, except that the proportions of the components in the second membrane layer slurry of this embodiment are adjusted to 31.06wt% of Ga-LLZO ceramic, 0.62wt% of PVDF-HFP, 6wt% of ethyl cellulose, and 62.32wt% of ethanol, and corresponding adjustments are made in preparation step 2.
[0095] Apart from this, all other parameters and steps remain unchanged.
[0096] Example 6
[0097] This embodiment is basically the same as Embodiment 1, except that the proportions of the components in the second membrane layer slurry of this embodiment are adjusted to 31.06wt% of Ga-LLZO ceramic, 0.62wt% of PVDF-HFP, 7wt% of ethyl cellulose, and 61.32wt% of ethanol, and corresponding adjustments are made in preparation step 2.
[0098] Apart from this, all other parameters and steps remain unchanged.
[0099] Example 7
[0100] This embodiment is basically the same as Embodiment 1, except that the proportions of the components in the second membrane layer slurry of this embodiment are adjusted to 31.06wt% of Ga-LLZO ceramic, 0.62wt% of PVDF-HFP, 5wt% of ethyl cellulose, and 63.32wt% of ethanol, and corresponding adjustments are made in preparation step 2.
[0101] Apart from this, all other parameters and steps remain unchanged.
[0102] Example 8
[0103] This embodiment is basically the same as Embodiment 1, except that the proportions of the components in the second membrane layer slurry of this embodiment are adjusted to 31.06wt% of Ga-LLZO ceramic, 0.62wt% of PVDF-HFP, 8wt% of ethyl cellulose, and 60.32wt% of ethanol, and corresponding adjustments are made in preparation step 2.
[0104] Apart from this, all other parameters and steps remain unchanged.
[0105] Example 9
[0106] This embodiment is basically the same as Embodiment 1, except that in the solid electrolyte membrane provided in this embodiment, the polymer in the first membrane layer is changed to PVDF-HFP, and corresponding adjustments are made in the preparation step 1.
[0107] Apart from this, all other parameters and steps remain unchanged.
[0108] Example 10
[0109] This embodiment is basically the same as Embodiment 1, with the only difference being that in the solid electrolyte membrane provided in this embodiment, the polymer in the second membrane layer is changed to PVDF, and corresponding adjustments are made in preparation step 2.
[0110] Apart from this, all other parameters and steps remain unchanged.
[0111] Comparative Example 1
[0112] This comparative example is basically the same as Example 1, except that the solid electrolyte membrane provided in this comparative example has only the first membrane layer, and accordingly, in the preparation steps of this comparative example, step 2 is omitted. In addition, other parameters and steps remain unchanged.
[0113] Comparative Example 2
[0114] This comparative example is basically the same as Example 1, except that the solid electrolyte membrane provided in this comparative example has only the second membrane layer, and accordingly, in the preparation steps of this comparative example, step 1 is omitted. In addition, other parameters and steps remain unchanged.
[0115] Comparative Example 3
[0116] This comparative example is basically the same as Example 1, except that when the solid electrolyte membrane provided in this comparative example is used in a lithium-ion battery, the stacking order of the first membrane layer and the second membrane layer is exchanged, that is, the first membrane layer is arranged close to the positive electrode sheet. Other than that, the other parameters and steps remain unchanged.
[0117] Comparative Example 4
[0118] This comparative example is basically the same as Example 1, except that the second film layer of the solid electrolyte membrane provided in this comparative example further contains Li TFS I, and in the slurry, the proportion of lithium salt is 2.0wt%, and accordingly, the proportion of ethanol solvent is changed to 60.11wt%, and the proportions of other components remain unchanged, and the preparation step 2 of this comparative example is adjusted accordingly. In addition, other parameters and steps remain unchanged.
[0119] Comparative Example 5
[0120] This comparative example is basically the same as Example 1, except that in step 2 of this comparative example, cellulose is replaced by methyl cellulose. Other parameters and steps remain unchanged.
[0121] Comparative Example 6
[0122] This comparative example is substantially the same as Example 1, except that in step 2 of this comparative example, ethanol is replaced by methanol. Other parameters and steps remain unchanged.
[0123] Comparative Example 7
[0124] This comparative example is basically the same as Example 1, except that in step 2 of this comparative example, PVDF-HFP is replaced by polyethylene oxide. Other parameters and steps remain unchanged.
[0125] Experimental example
[0126] The solid electrolyte membranes prepared in the above examples and comparative examples were subjected to the following tests, and the results are recorded in Tables 1 and 2.
[0127] Demolding condition: during the drying and demolding in step 1 and / or 2, the demolding condition is observed with naked eyes;
[0128] Film formation uniformity: Observe the obtained second film layer with naked eyes to observe the dispersion uniformity of particles on the film layer; Ionic conductivity detection method: Calculate the ionic conductivity by testing the bulk impedance R of the lithium battery according to the formula σ=l / RS, where l is the thickness of the film, R is the bulk impedance value, and S is the area of the film;
[0129] Symmetrical battery detection method: Assemble a battery with Li|solid electrolyte membrane|Li structure, and clamp the two sides with steel sheets to assemble a solid-state symmetrical battery, place it on the Xinwei software, set the current density for testing, and wait for the cycle.
[0130] The detection method of the number of cycles is as follows: assemble the button battery, place it on the Xinwei test software, set the charge and discharge rate, cut-off voltage and other test conditions, start the test, and wait for the cycle.
[0131] The specific assembly steps of the battery are as follows:
[0132] The positive electrode is a commercial mass-produced NCM811 positive electrode sheet with a loading of 15 mg / cm 2 The negative electrode is a 50-micron-thick metal lithium foil. The two layers of solid electrolyte membrane are cut into 16 mm discs, with the first membrane layer close to the negative electrode and the second membrane layer close to the positive electrode to form a sandwich structure, which is then packaged in a CR2032 button battery and left to stand for about 6 hours at room temperature to obtain a lithium metal battery.
[0133] Table 1
[0134]
[0135]
[0136] Table 2
[0137]
[0138]
[0139] It can be seen from the above table:
[0140] The batteries of Examples 1 to 10 all exhibit ionic conductivity, electrochemical window and number of cycles much higher than those of Comparative Examples 1 to 3, indicating that the solid electrolyte membrane with a composite structure provided in the present application has high ionic conductivity, strong high voltage resistance and electrochemical stability. When the solid electrolyte membrane is used in a battery, it helps to improve the cycle performance of the battery; further, the ionic conductivity, electrochemical window and number of cycles of Example 1 are much higher than those of Comparative Examples 1 to 3, which also shows that in the solid electrolyte membrane provided in the present application, the first film layer and the second film layer cooperate with each other to better improve the ionic conductivity, transmission performance and stability, which can greatly improve the cycle of the battery. At the same time, the first film layer faces the negative electrode and the second film layer faces the positive electrode, so that the solid electrolyte membrane can have good contact with the positive electrode and the negative electrode, respectively, which helps to improve the battery cycle.
[0141] The first film layer and the second film layer of Examples 1 to 10 can be completely demolded, and the second film layer has good film-forming uniformity. However, in Comparative Examples 1 to 7, the second film layer of Comparative Example 4 adheres to the PET substrate and the film formation is uneven. Comparative Examples 5-7 all have the situation that the second film layer cannot be demolded, and the film formation of the second film layer itself is also uneven. This shows that the present application optimizes the component types, uses ethyl cellulose and propyl cellulose as cellulose components, and uses ethanol as the solvent of the second film layer slurry, which helps to improve the film-forming effect and demoldability of the second film layer slurry.
[0142] The embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method and core idea of the present application. At the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A solid electrolyte membrane, characterized in that: The invention comprises a first film layer and a second film layer stacked together, wherein the first film layer is used to contact the negative electrode of the battery, and the second film layer is used to contact the positive electrode of the battery, wherein: The material of the first film layer includes a first polymer and a lithium salt; The material of the second film layer includes an inorganic ceramic filler, a second polymer and cellulose; Wherein, the cellulose includes one or more of ethyl cellulose and propyl cellulose; The first polymer and the second polymer are independently selected from one or more of PVDF and PVDF-HFP.
2. The solid electrolyte membrane according to claim 1, characterized in that The first polymer is selected from PVDF; and / or, The second polymer is selected from PVDF-HFP; and / or, The lithium salt includes one or more of LiTFSI, LiFSI, and LiClO4; and / or, The inorganic ceramic filler includes one or more of LLZTO and LLZGO.
3. The solid electrolyte membrane according to claim 1 or 2, characterized in that: In the material of the first film layer, the mass ratio of the first polymer to the lithium salt is (6-8):(2-3); and / or, In the material of the second film layer, the mass ratio of the inorganic ceramic filler to the second polymer is (30-31):(0.62-2); and / or, In the material of the second film layer, the mass ratio of the inorganic ceramic filler to the cellulose is (30-31):(6-7).
4. The solid electrolyte membrane according to claim 1, characterized in that The thickness of the first film layer is 10 to 20 μm; and / or, The thickness of the second film layer is 30-45 μm.
5. A method for preparing a solid electrolyte membrane according to any one of claims 1 to 4, characterized in that: The following steps are involved: Providing a first substrate, a second substrate, a first slurry and a second slurry; coating the first slurry on the first substrate to form a first film layer; coating the second slurry on the second substrate to form a second film layer; and, The first film layer and the second film layer are stacked to form a solid electrolyte membrane; The first slurry includes a first polymer, a lithium salt and a first solvent, the second slurry includes an inorganic ceramic filler, a second polymer, cellulose and a second solvent, the cellulose includes one or more of ethyl cellulose and propyl cellulose, and the first polymer and the second polymer are independently selected from one or more of PVDF and PVDF-HFP.
6. The preparation method according to claim 5, characterized in that: The first solvent comprises one or more of DMF and tetrahydrofuran; and / or, The second solvent comprises ethanol; and / or, The first polymer is selected from PVDF; and / or, The second polymer is selected from PVDF-HFP; and / or, The lithium salt includes one or more of LiTFSI, LiFSI, and LiClO4; and / or, The inorganic ceramic filler includes one or more of LLZTO and LLZGO.
7. The preparation method according to claim 5, characterized in that: The first slurry comprises the following components by weight percentage: 6-8% of a first polymer, 2-3% of a lithium salt, and the remainder being a first solvent; and / or, Calculated by mass percentage, the second slurry includes the following components: 30-31% inorganic ceramic filler, 0.62-2% second polymer, 6-7% cellulose, and the balance is a second solvent.
8. The preparation method according to claim 5, characterized in that: The step of coating the second slurry on the second substrate to form a second film layer includes: coating the second slurry on the second substrate, and then standing at 10-40° C. for 30-60 minutes to obtain a second film layer.
9. The preparation method according to claim 5, characterized in that: The step of coating the first slurry on the first substrate to form a first film layer includes: coating the first slurry on the first substrate, and then heating at 60 to 80° C. for 120 to 180 minutes to obtain the first film layer.
10. A lithium ion battery, characterized in that: It includes a positive electrode and a negative electrode arranged opposite to each other, and a solid electrolyte membrane arranged between the positive electrode and the negative electrode, the solid electrolyte membrane includes the solid electrolyte membrane described in any one of claims 1 to 4, or is prepared by the preparation method described in any one of claims 5 to 9, and the first membrane layer of the solid electrolyte membrane is arranged toward the negative electrode.
Citation Information
Patent Citations
Organic-inorganic composite electrolyte membrane and battery therewith
CN108695547A
Preparation method of composite solid electrolyte
CN114784372A
All solid lithium secondary battery and method for manufacturing the same
KR1020170141498A
Solid-state electrolyte, cathode electrode, and methods of making same for sulfide-based all-solid-state-batteries
US20230055896A1
Cited By
Solid-state electrolyte membrane and preparation method therefor, and lithium ion battery
WO2025251361A1
